Examining the Efficacy of Music Therapy in Alleviating Depression Among the Elderly - Iqbal , Muhammad; Olivia, Rastini (Insan Akademika Publications, 2024)
Depression poses a significant challenge to the well-being of elderly individuals, necessitating effective interventions beyond traditional pharmacotherapy. Through a rigorous mixed-methods design, the study explores the impact of music therapy interventions on depressive symptoms and quality of life in a sample of elderly participants recruited from community-based settings. The research employs a pre-post intervention design, with participants randomly assigned to either a music therapy intervention group or a wait-list control group. Quantitative assessments utilizing standardized measures, including the Geriatric Depression Scale (GDS) and the Short Form Health Survey (SF-36), are administered at multiple time points to evaluate changes in depressive symptoms and quality of life. Preliminary findings suggest promising results, with participants in the music therapy intervention group demonstrating significant reductions in depressive symptoms and improvements in overall quality of life compared to the control group. Quantitative analyses reveal statistically significant changes in depression scores and quality of life measures, while qualitative data offer nuanced narratives highlighting the therapeutic value of music therapy in promoting emotional expression, social connection, and personal growth among older adults. The implications of this research extend to theoretical frameworks, clinical practice, and policy development in geriatric mental health. By advancing our understanding of the therapeutic effects of music therapy and informing evidence-based practice guidelines, this study contributes to the integration of music therapy into comprehensive care models for older adults.